PENATALAKSANAAN NONINVASIF PROLAPSUS REKTI AKUT DENGAN AKUPUNKTUR NONINVASIF CHUZHEN: STUDI KASUS - Willie Japaries; Yelini Fan Hardi; Masluri Masluri; Aryaparana Nando (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2020)
Objective: This study is aimed at sharing our clinical experience in handling prolapsed rectum using the non-invasive Chuzhen acupuncture. In published journals, the Chuzhen acupuncture is also known as pestle needle therapy. Methods: This study is a single case report study of a patient with prolapsed rectum visiting our acupuncture clinic. The patient is a man of 60 years old, suffering from acute prolapsed rectum, after suffering from chronic haemorrhoids for over 10 years. After being explained about the therapy, he agreed to be treated with Chuzhen acupuncture. Results: After receiving 4 sessions of Chuzhen therapy within 2 weeks period, the prolapsed rectum retracted completely. No adverse effects were reported. After 6 months since the last therapy, the patient was followed up and he reported no relapse of the prolapsed rectum, based on the patient reported outcome measures (PROM). Conclusions: The present study showed that the non-invasive Chuzhen acupuncture was safe and effective in overcoming the prolapsed rectum as described in the case reported above.